Cultura e práticas de violência na sociedade rural norte-rio-grandense (1900-1930) - Freitas, Felipe Berté (2014)
The historiographical point of view of works that approach violence as an object of research are still very recent, especially considering the studies on rural societies that take as empirical base criminal cases. This type of documentation was receiving heuristic and investigative treatment from the 1970s and '80s, when the theoretical and methodological transformations of historiographical currents brought forth the valorization of new timeframes, themes, and subjects. In what concerns the Brazilian historiographical production, the pieces by Fausto, Chalhoub and Pesavento represent the first efforts towards understanding, through judiciary sources, the matter of the violence in the urban space bringing considerable theoretical and methodological for this field of study. However, such pieces do not take the violence as their mean subject of analysis, treating the matter as a reflection of the criminality and socialeconomical context of the first thirty years of the 20th century. In this sense, the conjuncture of the political, economic and social transition typical of Brazil and Rio Grande do Sul in this period of time, has brought forth conflicts in different places, such as, in the political parties relations, turning the society into a privileged space for the studying of violence. The criminal procedures present at Regional Hystorical Files of the University of Passo Fundo have allowed for a deeper analysis of these conflicts, bringing forth, consequently, another historical reality. In a rural society, characterized by values, behavioral patterns and sociocultural relations that made the assaults and murders a present element in social life, as the violence and custom habitus is constituted as a cultural practice. Thus, this thesis aims to demonstrate through the analysis of criminal cases filed homicide and bodily injury in the 1st Court of the Civil and Criminal District Court of Passo Fundo / Soledad during the period from 1900 to 1930, socio-cultural meanings of practices of violence represented in sources, its relations with the cultural practices and historical context of the period